2010
DOI: 10.3171/2010.5.focus10111
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar stimulation in the management of medically intractable epilepsy: a systematic and critical review

Abstract: Object The wide application of deep brain stimulation in the management of movement as well as other degenerative neurological and psychiatric disorders has renewed the interest in using deep brain stimulation in the management of medically intractable epilepsy. Various stimulation targets have been used with significantly varying results in aborting seizure activity. Electrical cerebellar stimulation (CS) has been used for more than 50 years in the management of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…The mechanism of action was originally thought to be thalamic inhibition via stimulation-induced Purkinje cell output, but this remains somewhat unclear [32]. In the 1970s, Cooper and colleagues were the first to report human cerebellar stimulation for epilepsy.…”
Section: Cerebellummentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of action was originally thought to be thalamic inhibition via stimulation-induced Purkinje cell output, but this remains somewhat unclear [32]. In the 1970s, Cooper and colleagues were the first to report human cerebellar stimulation for epilepsy.…”
Section: Cerebellummentioning
confidence: 99%
“…More rigorously controlled studies across 17 patients found none seizure free and 5/17 with reduced seizures. A detailed review on the patient has also recently been published [32].…”
Section: Cerebellummentioning
confidence: 99%
See 1 more Smart Citation
“…However, these initial studies yielded mixed results, with seizure termination not achieved in several studies. 19 The results from these early studies, including the absence of significant adverse effects, led to additional research into cerebellar stimulation in patients with medically refractory epilepsy.…”
Section: Cerebellummentioning
confidence: 99%
“…After numerous small clinical studies that produced promising results, 19 Van Buren et al 45 performed the first double-blind crossover study of 5 patients with medically intractable seizures in whom electrodes were placed on the superior surface of the cerebellum. The patients had a variety of partial and generalized seizures, with focal and/or bilaterally synchronous epileptiform discharges on EEG.…”
Section: Cerebellummentioning
confidence: 99%